How to Assured Quality in a Cloud and its Verification Process - Jain, Prince; Singh, Dr. Gurdev; Singh, Dr. Mandeep (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Cloud computing is discipline which use everything as service that provide economic, convenient and on-demand services to requested end users and cloud service consumer. Building a cloud computing network is not an easy task. It requires lots of efforts and time. For this, there arises a concept called Cloud Engineering. Cloud engineering is a discipline that uses set of processes which help to engineer a cloud network. The structure and principles of cloud engineering plays an important role in the engineering of usable, economic and vibrant cloud. The cloud engineering use a cloud development life cycle (CDLC) which systematic developed cloud. Quality assurance and verification is an important and mandatory part of development cycle. Quality assurance ensures the quality and web service of cloud network. Cloud Verification is an irrespirable step in a development of an economic cloud computing solution of a network. Verify the performance, reliability, availability, elasticity and security of cloud network against the service level agreement with respect to specification, agreement and requirement. The work in this paper focuses on the Quality Assurance factors and parameters that influence quality. It also discuses quality of data used in a cloud. This paper proposes and explores the structure and its component used in verification process of a cloud.